The Diverse Agendas Surrounding Nathan Chen on China's Social Media During the 2022 Beijing Winter Olympic Games: The Sport, the Athlete, and Nationalism - Qingning Wang (Journal of Current Chinese Affairs)
This paper analyses the online communication around American figure skater Nathan Chen (陈巍, Chen Wei ) on China's social media platform Sina Weibo during the 2022 Beijing Winter Olympic Games in order to critically unfold the agendas surrounding him. Engaging with agenda-setting theory and scholarship that conceptualises the contentious characteristics of China's online communication, and by using content analysis and network analysis, this paper presents empirical data to argue that online discussions around Chen were multiple and contentious. The communications consist of multiple topics surrounding the Games, the performances of different figure skaters, and the controversies surrounding Chen. The attitudes towards Chen were also diverse, such as nationalistic sentiments, appreciation of Chen's achievements, and disapproval of his performance all co-existed.